ENGENEERING ON THE (UN)PREDICATBLE ROADS - Hadži Jordanov, S.; Popovski, O. (Journal of Engineering & Processing Management, 2009)
A scope is given on the past and future progress of the Engineering. The origin of the term Engineering is elaborated and followed through the past. A stress is put on the Latin Ingenium, as oposed to the frequently mismatched origin in the word Engine. Further development through the Military until the Civil Engineering (and other varieties in the contemporary world) is distinguished too. A forecast is given on the possible direction of development in future, based on the experienced trends in the past.